Social and cultural relations in the inclusion of indigenous students in non-specific schools: Denominations and difficulties - Girotto, Rafaela Ferreira; Risso, Robison; Piovezana, Leonel (Seven Editora, 2024)
The text on social and cultural relations in the inclusion of indigenous students in non-specific schools: denominations and difficulties is also the result of a master’s dissertation in education that deals with the difficulties of non-indigenous schools to contemplate cultures in their specificities. Problem question: How are diversity and specific indigenous education addressed and developed in a non-specific school of indigenous culture? With the objectives of analyzing, in scientific productions and documents, the offer and development of intercultural education; Identify academic and bibliographic productions that deal with intercultural, specific, differentiated, bilingual and community indigenous school education; To interpose the Curricular Proposal of the state of Santa Catarina and the National Curriculum Reference for Indigenous Education; Mapping, starting from the origin of the indigenous students, culture, identity and choice for the school outside the Village; Identify the initiatives and possibilities that the school offers to indigenous students; To analyze the perceptions of indigenous students in relation to educational processes, the study was carried out and characterized as a qualitative research, supported by related bibliographic references, semi-structured interviews with teachers, public school directors and Kaingang students from the Xapecó Indigenous Land, located in the municipalities of Ipuaçu and Entre Rios SC. As a result, we identified failures and absence of pedagogical procedures that comply with the specific Brazilian legislation for the service of students from different cultures and the lack of specific training for teachers and school management, as well as the understanding of the processes of inclusion and citizenship formation for all people, without exception. DOI:https://doi.org/10.56238/sevened2024.010-055